2020
DOI: 10.1037/xhp0000713
|View full text |Cite
|
Sign up to set email alerts
|

The representational basis of positive and negative repetition effects.

Abstract: Repetition of target features in the same spatial location can either benefit or impair performance in perceptual tasks. Moreover, which of these two effects occurs can depend on whether an intervening event is presented temporally between consecutive targets. Here, we explored these effects for color feature repetitions by varying the representational overlap of consecutive targets. The second target on all experimental trials was a simple perceptual color. The task and first target were manipulated to vary t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 40 publications
0
3
1
Order By: Relevance
“…For example, we recently demonstrated that vocalizing a color had a profound impact on color repetition effects, while passive observation of the same symbolic representations did not . We further demonstrated that whether or not semantic color representations influenced a task depended on the underlying processes (Cochrane & Milliken, 2020). In other words, the difference between the present findings and those of Maljkovic and Nakayama may be due to subtle differences in the task − it may be that verbal anticipation of the upcoming target color influenced the processes underlying the PoP effect and subvocal utterances did not.…”
Section: Active and Passive Conscious Expectanciescontrasting
confidence: 51%
“…For example, we recently demonstrated that vocalizing a color had a profound impact on color repetition effects, while passive observation of the same symbolic representations did not . We further demonstrated that whether or not semantic color representations influenced a task depended on the underlying processes (Cochrane & Milliken, 2020). In other words, the difference between the present findings and those of Maljkovic and Nakayama may be due to subtle differences in the task − it may be that verbal anticipation of the upcoming target color influenced the processes underlying the PoP effect and subvocal utterances did not.…”
Section: Active and Passive Conscious Expectanciescontrasting
confidence: 51%
“…That is, imageryperception congruency effects also emerge in tasks where a centrally located stimulus has to be identified, which in principle cannot be due to attentional guidance. Instead, the preponderance of the influence here appears to occur at the response stage of processing ; although see Cochrane & Milliken, 2020). Further, the imagery congruency effects observed in binocular rivalry studies are purported to be of a retinotopic basis, which are not clearly attentional guidance or response based (Chang et al, 2013).…”
Section: Introductionmentioning
confidence: 81%
“…That is, there appeared to be a criterion shift towards responding quickly at the risk of making errors for the imagery congruent than incongruent color conditions when participants generated imagery with relatively low vividness. It may be that imagery with relatively low vividness hindered responding to the imagery congruent targets by producing a form of habituation like that underlying some negative repetition effects (see Cochrane & Milliken, 2020). Alternative and not mutually exclusive, it is also possible that participants used vividness ratings to reflect their performance more generallythat is, when participants made an error in the congruent color condition, this may have led them to report relatively low imagery vividness.…”
Section: Subjective Estimates Of Visual Imagerymentioning
confidence: 99%